If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 7(r + -3) Reorder the terms: 4 = 7(-3 + r) 4 = (-3 * 7 + r * 7) 4 = (-21 + 7r) Solving 4 = -21 + 7r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-7r' to each side of the equation. 4 + -7r = -21 + 7r + -7r Combine like terms: 7r + -7r = 0 4 + -7r = -21 + 0 4 + -7r = -21 Add '-4' to each side of the equation. 4 + -4 + -7r = -21 + -4 Combine like terms: 4 + -4 = 0 0 + -7r = -21 + -4 -7r = -21 + -4 Combine like terms: -21 + -4 = -25 -7r = -25 Divide each side by '-7'. r = 3.571428571 Simplifying r = 3.571428571
| -36=3(x-3)-6x | | 4-5y=-20 | | 9=6(q-6) | | 0=-0.09+1.1x | | 7x-2(4x+23)+12= | | 5+7=2x | | -6(-3)-7(2)=4 | | 2(y+5)-4y=16 | | 3n-n+5= | | 5+2(2x-5)=-2+3(x-2) | | 2x-5x=-1-5 | | -4x-8=3x-17 | | 750+30x=y | | -9(a+6)=2 | | y=-3.3x-3.3 | | x+x+11=37 | | 2(2x+1)+x=-39 | | y=-2x^2-24x-20 | | -9=m-98 | | Y^2+21y=0 | | 13=-7+r | | 4x-35=25 | | -1(x+3)=2x-12 | | -3(6-5x)=27 | | -8(p-9)=6 | | 32+4n=96 | | (x*8)-(x*3)=60 | | -6.3-2.3b=26.13 | | 56x+8y=24 | | 5+7y=82 | | -3(j+4)=8 | | f+4=11 |